2019
DOI: 10.1590/1806-3713/e20180181
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profile of non-small cell lung cancer in northeastern Brazil

Abstract: Objective: To investigate the histological subtypes and mutational profiles of non-small cell lung cancer in Brazil, looking for correlations among histological subtypes, expression of anaplastic lymphoma kinase (ALK), EGFR mutation status, and programmed death-ligand 1 (PD-L1) expression. Methods: We evaluated 173 specimens obtained from patients with lung adenocarcinoma in northeastern Brazil. Expression of PD-L1 and ALK was evaluated by immunohistochemistry; EGFR mutation status was evaluated by sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Despite the theoretical rationale supporting this association, we did not identify a relationship between PDL1 and GSK-3b scores in our cohort. A recent publication about the positivity of PDL1 in the same region of northeastern Brazil showed that 59.5% of patients were PDL1 negative (43). Matsuo et al studied the importance of AKT, mTOR, and GSK3 in the occurrence of lymph node involvement in oral cavity squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the theoretical rationale supporting this association, we did not identify a relationship between PDL1 and GSK-3b scores in our cohort. A recent publication about the positivity of PDL1 in the same region of northeastern Brazil showed that 59.5% of patients were PDL1 negative (43). Matsuo et al studied the importance of AKT, mTOR, and GSK3 in the occurrence of lymph node involvement in oral cavity squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In Latin America, a study enrolling 5,130 NSCLC patients from 10 countries (excepting Brazil), the frequencies of ALK rearrangements ranged from 4.1% to 10.8% (Colombia 4.1%; Panama 4.4%; Uruguay 5.4%; Argentina 6.0%; Mexico 7.6%; Chile 8.6%; Venezuela 8.9%; Costa Rica 9.5%; Peru 10.8%) (34). In Brazil, two recent studies employing immunohistochemistry, one from Northeast and another from South, reported frequencies of ALK rearrangements of 10.4% (n=173 patients) and 4% (n=275 patients), respectively (10,12). The frequency of ALK rearrangements in the present work is in between other Brazilian studies.…”
Section: Discussionmentioning
confidence: 99%
“…Other driver genomic alterations are ALK, RET, and ROS1 rearrangements, which can also be targeted for tyrosine kinase inhibitors (TKIs) (2,9). Although these genetic rearrangements are actionable, and the frequency of them is broadly investigated worldwide, the frequency of RET and ROS1 rearrangements is unknown in Brazilian patients (10)(11)(12). Moreover, Brazilian patients have a high admixture background, with contribution from European, African, Native American (Amerindian), and, more recently, Asian ethnicities (8,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some laboratories prefer NGS technologies, [162][163][164] sequencing 14-20 genes at one time, 124,162,165 whereas others have adopted strategies to improve TAT by using RT-PCR assays for EGFR and BRAF mutations, 162,[164][165][166] and IHC/FISH for ALK, ROS1 and PD-L1 rearrangements. 163,164,167 In the absence of government reimbursement for molecular testing, several pharmaceutical companies have recently established a national "Lung Mapping" consortium. The consortium provides oncologists with access to a subsidized NGS-based test using the FoundationOne ® platform and has considerably improved access to testing in several Brazilian centers.…”
Section: Brazilmentioning
confidence: 99%